2020
DOI: 10.3390/jcm9041049
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Lymphocyte Phenotype Differentiates Secondary Antibody Deficiency in Rheumatic Disease from Primary Antibody Deficiency

Abstract: The phenotype of primary immunodeficiency disorders (PID), and especially common variable immunodeficiency (CVID), may be dominated by symptoms of autoimmune disorders. Furthermore, autoimmunity may be the first manifestation of PID, frequently preceding infections and the diagnosis of hypogammaglobulinemia, which occurs later on. In this case, distinguishing PID from hypogammaglobulinemia secondary to anti-inflammatory treatment of autoimmunity may become challenging. The aim of this study was to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Patients with CVID and SLE both had lymphopenia. We found that only a more detailed analysis of peripheral lymphocyte subset counts showed differences; specifically, smB cells and plasmablasts were reduced in CVID, which is in agreement with other studies [ 30 ]. Therefore, low smB cells detected in patients with autoimmunity should increase the awareness of immunodeficiency.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Patients with CVID and SLE both had lymphopenia. We found that only a more detailed analysis of peripheral lymphocyte subset counts showed differences; specifically, smB cells and plasmablasts were reduced in CVID, which is in agreement with other studies [ 30 ]. Therefore, low smB cells detected in patients with autoimmunity should increase the awareness of immunodeficiency.…”
Section: Discussionsupporting
confidence: 93%
“…Until now, studies comparing B and T cell subsets from patients with PID and patients with rheumatic diseases are limited. In one study, patients with primary and secondary hypogammaglobulinemia in the course of different rheumatic diseases were observed [ 30 ]. Another study involved the analysis of polymyalgia rheumatica patients treated with systemic glucocorticoids [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of tolerability would be especially relevant in view of the immunosuppressive effect of diverse csDMARDs and dDMARDs, which may worsen the PAD-intrinsic immunodeficiency. 54 41 In the present study, only a minority of patients developed infectious complication as a consequence of their arthritis treatment, which may underestimate the impact of DMARDs and their immunosuppressive effect on patients’ immunodeficiency. The latter may depend on several parameters, including concomitant glucocorticoid treatment, the type of PAD as well as the vaccination status of tested patients, which should be evaluated through perspective studies with large numbers of treated patients.…”
Section: Discussionmentioning
confidence: 67%
“…Whole blood was collected in ethylene diamine tetraacetic acid (EDTA) tubes, and peripheral blood mononuclear cell (PBMC) preparations have been performed as described previously ( 23 ). PBMCs were cryopreserved in freezing medium (heat-inactivated fetal calf serum (FCS), PAN-Biotech; 10% v/v dimethyl sulfoxide, Sigma) until use.…”
Section: Methodsmentioning
confidence: 99%
“…To calculate standardized incidence ratios (SIRs), all patients were stratified by age and gender. Data on the reference population were derived from the 12th edition of the “Cancer in Germany” report by the Robert Koch Institute ( 23 ). The expected number of cases for each type of cancer in the studied patient cohort was calculated based on the age- and gender-specific incidence rate provided in the aforementioned report.…”
Section: Methodsmentioning
confidence: 99%